Screening of Primary School Children for Amblyopia and Amblyogenic Factors in Central Cairo, Egypt - Mohammad A. Rashad; Khaled M. Abd Elaziz; Samah Mahmoud Fawzy; Ahmed Abdel Meguid Abdel latif; Mahmoud Abdel Meguid Abdel latif (Journal of Ophthalmology)
Objective. To measure the prevalence of amblyopia and amblyogenic factors among primary school children and to evaluate distance visual acuity (VA) as a screening test to detect amblyopia and define its cutoff value. Subjects and Methods. A cross-sectional study was conducted on primary school children in two schools in Central Cairo. Children underwent assessment of visual acuity using Landolt broken ring. Comprehensive ophthalmologic examination was performed for amblyopia suspects at the Ophthalmology Department of Ain Shams University Hospitals, including reassessment of best-corrected visual acuity (BCVA) using the same chart. Results. A total of 352 children were examined. Reduced screening VA (amblyopia suspect) was detected in 47 subjects (13.35%) proved amblyopia after comprehensive examination was 1.98% (7 cases). Refractive errors (REs) were present in all suspected and proved amblyopia cases (100%) but was only present in 11.6% of nonamblyopic students (P<0.05). The prevalence of hyperopia in the whole sample was 3.6%, and was 27.6% in subjects with RE. Thirty percent of hyperopic eyes were amblyopic. The prevalence of myopia was 9.3% of the whole sample and 70% of students with RE. Only 9% of myopic eyes were amblyopic. Mild to moderate amblyopia (VA better than 0.2log MAR) was 42.9%, while severe amblyopia represented 57.1%. Conclusion. This study emphasizes the importance of school-based eye care system targeting the detection of amblyopia by application of a fast screening distance VA test with a cutoff value of high sensitivity at log MAR 0.539 (Snellen′s VA equivalent 6/18).